Difficulties with diagnosis and consequential poor outcome due to stigma of acquired immunodeficiency syndrome - a case report. (1st September 2013) - Vuletic, Vladimira; Nevajda, Branimir; Spero, Martina; Chudy, Darko
Abstract : Low incidence of human immunodeficiency virus (HIV) infections and acquired immunodeficiency syndrome (AIDS) has been detected in Croatia so far. Toxoplasmic encephalitis (TE) is the most common opportunistic cerebral infection in AIDS patients and is highly responsive to antiparasitic chemotherapy, if treated at an early stage. We present the case of the brain biopsy confirmed as TE on a 36-year-old female patient who at admission presented with unconsciousness and a right hemiplegia. A MSCT was performed and two hypodense lesions were diagnosed. The patient's family initially denied the presence or history of any medical problem or infection. An MRI showed multiple ring-enhanced mass lesions. An infectologist required a brain biopsy to exclude cerebral lymphoma and multiple metastases. Pathohistological analysis suggested TE. Meanwhile, patient's blood samples were found to be HIV positive. The patient was transferred to University Hospital for Infectious Diseases in Zagreb, where she died 2 days following admission. The patient's family terminally confessed that the patient had been HIV positive for 10 years and had refused any treatment. Family's denial of infection as well as 'hiding information' concerning patient's health from physicians involved in her treatment caused a delay in proper on-time patient treatment. We would like to emphasize that TE must be considered as a differential diagnosis in patients presenting with multiple cerebral lesions, including patients without acknowledged past history of HIV infection. A stigma towards HIV infection and ignorance of the disease still exist and therefore hinders proper treatment.